Electric Vehicles: Innovation Process for Sustainable Development and Future Market Forecasting - Ahmed Aboazoum (Information Technology and Science (ITScience), 2022)
Conventional vehicles are a threat to environmental pollution, as the emission of the gasses from the vehicles using fossil fuel affects the whole environment. This concern has led the researchers and inventors to work upon the study of electric vehicles. Electric vehicles are said to be incorporating as the approach for decarbonisation and environment friendly transportation system. The contemporary world is emerging its focus on the Electric Vehicles as an alternative of the old school vehicles they emit harmful gasses. This paper focuses on the invention and innovation of the electric vehicles as they not only reduce the noise pollution, air pollution and greenhouse gas emissions but also focuses on the economic sustainability keeping the inflation across nations in mind. Hence, the study soaks data from the available literature in order to have point of view regarding how Electric Vehicles play a role in sustainable development and further talks about the future market of these vehicles that depends upon its sustainability.